Signaling Functions of Intramembrane Aspartyl-Proteases - Papadopoulou, Alkmini A.; Fluhrer, Regina (Frontiers in Cardiovascular Medicine, 2020)
Intramembrane proteolysis is more than a mechanism to “clean” the membranes from proteins no longer needed. By non-reversibly modifying transmembrane proteins, intramembrane cleaving proteases hold key roles in multiple signalling pathways and often distinguish physiological from pathological conditions. Signal peptide peptidase (SPP) and signal peptide peptidase-like proteases (SPPLs) recently have been associated with multiple functions in the field of signal transduction. SPP/SPPLs together with presenilins (PSs) are the only two families of intramembrane cleaving aspartyl proteases known in mammals. PS1 or PS2 comprise the catalytic centre of the γ-secretase complex, which is well studied in the context of Alzheimer’s disease. The mammalian SPP/SPPL family of intramembrane cleaving proteases consists of five members: SPP and its homologous proteins SPPL2a, SPPL2b, SPPL2c and SPPL3. Although these proteases were discovered due to their homology to PSs, it became evident in the past two decades that no physiological functions are shared between these two families. Based on studies in cell culture models various substrates of SPP/SPPL proteases have been identified in the past years and recently-developed mouse lines lacking individual members of this protease family, will help to further clarify the physiological functions of these proteases. In this review we concentrate on signalling roles of mammalian intramembrane cleaving aspartyl proteases. In particular, we will highlight the signalling roles of PS via its substrates NOTCH, VEGF and others, mainly focusing on its involvement in vasculature. Delineating also signalling pathways that are affected and/or controlled by SPP/SPPL proteases. From SPP’s participation in tumour progression and survival, to SPPL3’s regulation of protein glycosylation and SPPL2c’s control over cellular calcium stores, various crossovers between proteolytic activity of intramembrane proteases and cell signalling will be described.